Onset of Time of Ischaemic Stroke among Elderly Patients in Bangladesh - Ara, Kazi Jannat; Islam, Rofiqul; Habib, Ahsan; Ahmed, Anis; Rahman, Hafizur; Fatema, Nilufar (University Heart Journal, 2018)
Stroke is ranked as the third leading cause of death in Bangladesh. According to the World Health Organization, mortality rate of Bangladeshi population due to stroke as number 84 in the world. The reported prevalence of stroke in Bangladesh is 0·3%, although no data on stroke incidence have been recorded. There is no well-documented data of the time of onset of ischaemic stroke. This study was done to find out timing and relationship with activity among elderly ischaemic stroke patients. This cross sectional study was conducted in Out Patient department (OPD) stroke clinic and Indoor of the department of neurology, BSMMU, Dhaka from July 2015 to June 2016. A total 200 patients suffering from ischaemic stroke within the range of 61-95 years of age of both sexes were included. Patient with TIA, hemorrhagic stroke and stoke after one month of onset were excluded. Male and female ratio was 1.95:1. Mean age was 68.4±8.24 years. clinical presentation of the patients. Hemiparesis was presented in 66.2% patients followed by 57.0% patients were inability to talk, 33.8% presented with hemiplegia, 20.4% had vertigo, 9.2% had headache, 7.0% had vomiting, 2.8% had loss of consciousness and 2.1% had convulsion. Maximum incidences were occurred during sleep (36.6%), during day to day activity 39.4% and resting condition (21.8%) respectively. University Heart Journal Vol. 14, No. 1, Jan 2018; 28-30